2007
DOI: 10.1016/j.cardiores.2007.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion injury in humans: A review of clinical trials on reperfusion injury inhibitory strategies

Abstract: The principal therapy in patients with myocardial infarction to limit infarct size is myocardial reperfusion by mechanical or pharmacological intervention. Reperfusion has been proposed to cause myocardial injury beyond that caused by the preceding ischaemia, termed "reperfusion injury" (RI). While the precise mechanism of RI is still incompletely understood, a large number of clinical studies have been performed over the past decade targeting some of the postulated mechanisms of RI. These clinical studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 129 publications
2
121
0
3
Order By: Relevance
“…Nevertheless, the clinical trial data had not confirmed their universal efficiency established in experimental researches [10,11]. Inconsistency of the clinical results of testing antioxidants was explained by difference of the used models of lesions on animals and cell from the human body environment [1,5], by incorrect choice of the tested antioxidant, parameters of monitoring its activity, amounts of the injected derivative doses, duration of trials, patient selection criteria [9,11]. Such situation determines the necessity to perform new clinical trials according to the strict protocol with more wide use of new antioxidant derivatives.…”
Section: Experimental and Clinical Antioxidant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the clinical trial data had not confirmed their universal efficiency established in experimental researches [10,11]. Inconsistency of the clinical results of testing antioxidants was explained by difference of the used models of lesions on animals and cell from the human body environment [1,5], by incorrect choice of the tested antioxidant, parameters of monitoring its activity, amounts of the injected derivative doses, duration of trials, patient selection criteria [9,11]. Such situation determines the necessity to perform new clinical trials according to the strict protocol with more wide use of new antioxidant derivatives.…”
Section: Experimental and Clinical Antioxidant Researchmentioning
confidence: 99%
“…One of the objectives of adjacent (additional) therapy is to block it. The oxidative stress contributes to the aggravation of disorders during thrombolysis for potency of infarct-related artery ("reperfusion injury") [5,6], during vascular angioplasty procedures (development of restenosis) [7,8]. That's why the importance of search of highly efficient resources to ensure antioxidant protection of the cardiovascular system is well known and justified.…”
Section: Introductionmentioning
confidence: 99%
“…Многочисленные исследования свидетельствуют об успешном примене-нии первых двух подходов и в снижении частоты леталь-ных исходов, и в уменьшении степени ремоделирования миокарда и риска развития СН. Применение же различ-ных подходов, направленных на уменьшение окисли-тельного стресса, в основном не привели к положитель-ным результатам [5]. Тем не менее такие подходы про-должают разрабатываться.…”
Section: Discussionunclassified
“…Intravascular fluid resuscitation is the consensual treatment for patients with hypovolemic shock (1). This lifesaving procedure may, on the other hand, induce ischemia and reperfusion (I-R) injury in cells of virtually any vital organ (2).…”
Section: Introductionmentioning
confidence: 99%